INTERNALISASI NILAI-NILAI ISLAM MELAYU DALAM PENDIDIKAN AGAMA ISLAM INKLUSIF SEBAGAI PENGUATAN MODERASI BERAGAMA - Siti Banati Sholiha; Hanifantun Nisa; Fitrioviyanti; Lenymarlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic Religious Education (PAI) plays a strategic role in shaping students who are not only religious but also capable of living harmoniously in a pluralistic society. However, in practice, PAI learning often emphasizes cognitive aspects and pays less attention to affective dimensions and the development of moderate religious attitudes. This condition may lead to exclusive and less tolerant religious understanding. Therefore, an innovative approach is needed through inclusive Islamic Religious Education that integrates local wisdom values, particularly Malay Islamic values, to strengthen religious moderation. This study employs a qualitative approach using library research. The data were collected from various relevant sources, including academic journals, books, and official documents related to religious moderation, inclusive Islamic education, and Malay Islamic values. Data collection was conducted through documentation techniques, while data analysis used content analysis methods involving data reduction, data display, and conclusion drawing. This approach aims to explore concepts, strategies, and the relevance of internalizing Malay Islamic values in education. The findings reveal that Malay Islamic values such as tolerance, moderation, justice, and social harmony are highly relevant in strengthening religious moderation through inclusive PAI. The internalization process is carried out through three stages: value transformation, value transaction, and transinternalization, which effectively shape students’ tolerant and open-minded character. This approach not only impacts individuals but also contributes to creating an inclusive educational environment, strengthening social cohesion, and preventing radicalism. Thus, integrating Malay Islamic values into inclusive Islamic Religious Education is an effective strategy for developing moderate and civilized education.